Job Demands, not resources, predict worsening psychological distress during the early phase of the COVID-19 pandemic - Knight, Caroline; Keller, Anita; Parker, Sharon (Taylor & Francis, 2022)
The COVID-19 pandemic forced many workers globally to work from home, suddenly, and often without choice, during a highly uncertain time. Adopting a longitudinal, person-centered approach, we explored patterns of change in employees’ psychological distress over three months following the early phase of the pandemic. We investigated how change in distress unfolded for different latent subgroups. We modelled whether and how work characteristics, and individuals’ degree of detachment from work, predicted membership of different distress trajectories. Growth mixture modelling revealed two distress profiles: (i) a declining distress profile where employees experienced reduced distress over time, suggesting adaptation and/or improved coping; (ii) a rising distress profile where distress increased and eventually plateaued, suggesting a stress reaction process followed by adaptation. Employees with high workload, underload, or close monitoring, were more likely to belong to the rising distress profile. Detachment from work buffered the negative effect of workload and close monitoring on distress profile membership. Scheduling autonomy and colleague support did not predict profile membership. Contrary to predictions, manager support predicted membership in the rising distress profile. Our findings extend theoretical understanding of how distress unfolds over time, and show the importance of particular job demands in explaining these change processes.